Experimental Analysis of Self Compacting Concrete using Bagasse Ash, Metakaolin and Glass Fiber - Wagh, Monali; U. P. Waghe; Anshul Nikhade; Harshal Nikhade (Engineering Access, 2026)
Self-compacting concrete (SCC) is a concrete that has the capacity to flow under its own weight without segregation. SCC has the ability to pass through the closed reinforcement, fill all the spaces of the formwork without segregation. In India, industrial and agricultural waste are produced in large quantities. Use of these wastes as a replacement for cement or sand gives a solution to the problem of disposal of these wastes. It decreases the cost of the structure as well as CO2 emissions. This project is aimed at identifying the optimum amount of agricultural waste bagasse ash and metakaolin as replacements for cement with and without 0.1% GF and compared the fresh and strength properties of self-compacting concrete with the control mix. The result shows that the SCCB10M5 mix has better flowability as compared to others, and the strength properties were highest for the SCC1B10M5 mix.